การศึกษาการบริหารหลักสูตรและงานวิชาการโรงเรียนประถมศึกษาเอกชนที่ได้รับรางวัลพระราชทาน - ภัทรา โง้วอมราภรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this research was to study the curriculum and academic administration in private primary schools with the Royal Award in Bangkok. The samples of the study were 3 private schools used purposive sampling. The data was obtained from the administrators and academic staff in total of 45. The research instruments were the semi-structured interview, the observation form and the documents study. The data were analyzed by content analysis and proposed in descriptive presentation. The research findings were as follows: 1) The administrators and academic staff directed, monitored, supervised and evaluated the curriculum implementation and brought the assessment results to improve the curriculum in each academic year. 2) The teachers analyzed the students individually, planned and managed the teaching and learning preparation to make students think critically and practise. 3) The administrators encouraged the teachers to be knowledgeable in measurement and evaluation, reported the results and applied them. 4) The administrators provided the service and encouraged the teachers to share and improve themselves in learning material using. 5) The teacher provided the activities based on student’s interest to develop their skills and encouraged desired characteristic including provided the services to solve the students’ problems. 6) The administrators, teachers and staff supported and provided activities to fulfil students’ learning by making projects and expand learning resources in schools.